Antenatal intimate partner violence and breastfeeding practices: Evidence from a national longitudinal study in Ethiopia - Zelalem Nigussie Azene; Berihun Dachew; Nicole Reilly; Solomon Abrha Damtew; Catherine MacPhail (PLoS ONE, 2026)
Background Intimate partner violence (IPV) is a widespread public health concern that disproportionately affects women of reproductive age, particularly during pregnancy. Antenatal IPV (AN-IPV) is associated with adverse maternal and infant health outcomes, including poor breastfeeding practices. In Ethiopia, despite the high prevalence of AN-IPV, its association with breastfeeding outcomes remains poorly understood. Therefore, this study aimed to investigate the relationship between AN-IPV and breastfeeding indicators in Ethiopia. Methods Data from the Performance Monitoring for Action (PMA) Ethiopia, a nationally representative survey conducted between November 2021 and October 2022, were used. A total weighted sample of 1, 610 postpartum mother-child pairs was included. Data collected at baseline (during enrolment) and six weeks postpartum were used for this analysis. We fitted multilevel binary logistic regression models to estimate the associations between any AN-IPV, as well as physical and sexual AN-IPV separately, and early initiation of breastfeeding (EIBF) and exclusive breastfeeding (EBF), accounting for clustering within enumeration areas. Adjusted Odds Ratios (AORs) with 95% Confidence Intervals (CIs) were calculated to examine associations, and two-sided p-values (<0.05) were used to determine statistical significance. Results The prevalence of AN-IPV among mothers was 10.2%, with 6.9% reporting sexual AN-IPV and 4.4% reporting physical AN-IPV. Mothers exposed to any form of AN-IPV had a lower likelihood of initiating breastfeeding within the first hour of birth (AOR = 0.60, 95% CI: 0.36–0.99). Sexual AN-IPV was also associated with a reduced likelihood of EIBF (AOR = 0.50, 95% CI: 0.26–0.95, Model 2); however, this association did not remain in the fully adjusted model (AOR = 0.54, 95% CI: 0.28–1.04, Model 3). We found no evidence of an association between AN-IPV and EBF at six-weeks postpartum. Conclusions Our study revealed that maternal exposure to any form of AN-IPV (physical or sexual) was associated with reduced EIBF. However, no association was observed between AN-IPV and EBF at six weeks postpartum. The findings highlight the need for routine identification of women who have experienced or are experiencing AN-IPV, and for the development and provision of targeted, trauma-informed interventions aimed at supporting optimal breastfeeding practices.